2016
DOI: 10.1080/03091902.2016.1213907
|View full text |Cite
|
Sign up to set email alerts
|

Value propositions of mHealth projects

Abstract: While mHealth holds great potential for addressing global health disparities, a majority of the initiatives never proceed beyond the pilot stage. One fundamental concern is that mHealth projects are seldom designed from the customer's perspective to address their specific problems and/or create appreciable value. A customer-centric view, where direct tangible benefits of interventions are identified and communicated effectively, can drive customer engagement and advance projects toward self-sustaining business… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 8 publications
0
25
0
Order By: Relevance
“…In Gorski et al [17] the authors address this issue by analysing the downstream value proposition and attempting to design from the customers’ perspective to address their specific problems and/or create appreciable value. The authors suggest that a customer-centric view, where direct tangible benefits of interventions are identified and communicated effectively, can drive customer engagement and advance projects toward self-sustaining business models.…”
Section: Overview Of Articles In This Special Issuementioning
confidence: 99%
“…In Gorski et al [17] the authors address this issue by analysing the downstream value proposition and attempting to design from the customers’ perspective to address their specific problems and/or create appreciable value. The authors suggest that a customer-centric view, where direct tangible benefits of interventions are identified and communicated effectively, can drive customer engagement and advance projects toward self-sustaining business models.…”
Section: Overview Of Articles In This Special Issuementioning
confidence: 99%
“…Deglise et al published a systematic review on short messaging service (SMS) interventions for disease prevention and demonstrated that these mHealth projects were concentrated mostly in South Africa, Kenya and India [ 15 ]. Also, Gorski et al (2016) found from their meta-analysis that globally, most mHealth projects are located in sub-Saharan Africa [ 16 ]. According to Njoroge et al (2017), the growth of mHealth in sub-Saharan Africa is particularly outstanding in Kenya [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Third, compared to other regions, sub-Saharan Africa has been known to be the place with burgeoning supply and demand for m-health. 12 The growth of m-health in sub-Saharan Africa over the past decade proved that several countries in this region such as Kenya and South Africa are ready to lead the m-health initiative globally. 9 …”
Section: Discussionmentioning
confidence: 99%
“…Also, a dummy variable for sub-Saharan African country versus others was included as the m-health is growing most rapidly in sub-Saharan Africa, but at the same time, resources are more limited in this region. 12 Last, a country's gross national income (GNI) per capita was included as a covariate to control for the effect of size of a country's economy on m-health policy readiness.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation